1974
DOI: 10.1111/j.1476-5381.1974.tb08576.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marihuana in Laboratory Animals and in Man

Abstract: 1The pharmacological potencies of the resins from three different samples of Brazilian marihuana (A, B and C) were determined through corneal areflexia in rabbits, decrease of spontaneous motor activity and induction of catatonia in mice, and decrease of rope climbing performance of rats. 2 The A9 -tetrahydrocannabinol (A9 THC) content of the marihuanas, measured by gas chromatography, was 0.82, 2.02 and 0.52%, respectively, for samples A, B and C. Approximately 2% cannabinol was present in samples A and B whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

1977
1977
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 21 publications
6
33
0
1
Order By: Relevance
“…The results agree with those from our cataleptic work with THC, herb and extracts (Fairbairn & Pickens, 1981) and with those of Carlini et al, ( 1974) (7) (7) (7)…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results agree with those from our cataleptic work with THC, herb and extracts (Fairbairn & Pickens, 1981) and with those of Carlini et al, ( 1974) (7) (7) (7)…”
Section: Discussionsupporting
confidence: 82%
“…I have attempted to discover whether the 0007-1188/81/040649-08 $01.00 sedative action of 'whole' herb and extracts is related to their THC contents measured by gas-liquid chromatography (g.l.c. ) analysis, by the method of Fairbairn & Liebmann (1973), as previous work has shown that the herb and extracts are at least two or four times more active than one would expect from their THC content (Carlini et al, 1974;Fairbaim & Pickens, 1981). The effect of aspirin on sedative action and its reversal by prostaglandin E2 (PGE2) has also been determined since previous work showed that the cataleptic effects of herb and extracts were antagonized by aspirin and restored by PGE2 (Fairbaim & Pickens, 1979;1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and because of the large biological variation which accompanies cannabis work (Carlini et al, 1974) and which is confirmed from our data (see Table 1) where the lowest score was zero (from a non-reacting mouse) and the highest score 270. One way of overcoming the difficulty is to study those factors which cause the 'day to day' variance and this we have done for the ring test (Fairbaim & Pickens, 1980).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly in animals it has never been possible to explain all the effects of the crude material in terms of THC alone (Mechoulam, Ben-Zvi, Shani, Zemler, Levy, Edbury & Grunfeld, 1972;Carlini, Masur, Karniol & Leite, 1972). However, in both man (Isbell, 1971;Carlini, Kamiol, Renault & Schuster, 1974) and in animals (Carlini et al, 1974) the activity of the herb and extracts is proportional to their THC contents. In an attempt to establish the ratio of the content of THC to the biological activity we have made use of the fact that the cataleptic effect of very small doses of THC given orally can be measured in mice and that the cataleptic effect is dependent on the availability of prostaglandins E2 (PGE2) (Fairbairn & Pickens, 1979;.…”
Section: Introductionmentioning
confidence: 99%